Pengaruh Pemberian Bubur Labu Kuning dan Daging Ayam Terhadap Peningkatan BB pada Bayi Gizi Kurang - Podungge, Yusni; Rasyid, Puspita Sukmawaty (Universitas Gorontalo, 2018)
Undernutrition in infants is a condition where the baby does not growand develop optimally because of the unfulfilled intake of nutritionsubstances in the body. Under-nutrition in infants can be overcome bythe provision of balanced nutritious foods, one sign of improvednutrition can be seen from normal weight gain for age. One of the foodsthat can boost the improvement of nutrients is a food that containsproteins and vitamins, such as yellow pumpkin and chicken, whereyellow pumpkin contains vitamin A and chicken meat as a source ofanimal protein that contains good nutrients. The purpose of this studywas to analyze the effect of yellow pumpkin and chicken meat onweight growing infant 12 months in work area of Talaga JayaCommunity Health Center. The research method used experimentalresearch model with design non equivalent control group for eachgroup of intervention and control. Sampling using purposive samplingaccording to inclusion and exclusion criteria. With a sample number of30 malnourished infants less than 12 months of age. Analyticaltechniques was used in the chi square test. The result of this researchwas showed that value of chi square count 22,634 highger than chisquare table Df 1 = 3,841. There was influence giving yellow pumpkinpumper and chicken to enhancement nutritional weight infant weight12 month in work area Puskesmas Talaga Jaya. The conclusion wasthe provision of pumpkin porridge can raise the weight of infants lessthan 12 months of age as a benchmark nutritional improvements ininfants less nutrition.